Penolakan Majelis Hakim Terhadap Permohonan Pembatalan Akta Jual Beli yang Cacat Syarat Subjektif: Studi Putusan No. 32/Pdt.G/2019/PN Kpn - Syam’ani, Nessa Isabela; Setiawan, I Ketut Oka (SIGn Jurnal Hukum, 2025)
Disputes concerning the validity of a deed of sale due to alleged subjective requirement defects constitute a significant problem within agrarian and contract law. This research aims to analyze the legal reasoning (ratio decidendi) of the Panel of Judges in Decision Number 32/Pdt.G/2019/PN Kpn, which denied the application for the annulment of Deed of Sale Number 302/Kec.Bululawang/1993, despite allegations of a subjective defect arising from the seller having passed away before the deed was executed. Employing a normative legal research method integrating case study, statute, and conceptual approaches, a qualitative analysis was conducted on the said decision. The analysis results indicate that the Panel of Judges’ denial was not based on a direct examination of the Deed of Sale Number 302/Kec.Bululawang/1993 due to the subjective defect under Article 1320 of the Civil Code. Instead, the dominant ratio decidendi rested upon the validation of the Sale Agreement under seal dated 5 July 1983 and the application of the doctrines of prescription and rechtsverwerking resulting from over 30 years of good faith physical possession. It is concluded that Decision Number 32/Pdt.G/2019/PN Kpn affirmed Defendant 1’s ownership through the mechanism of lapse of time while prioritizing pragmatic legal certainty, although leaving juridical ambiguity regarding the status of Deed of Sale Number 302/Kec.Bululawang/1993 indicates a judicial tendency to prioritize the substance of long-term possession over formal defects in deeds within belatedly filed disputes.